Sanctum Rasa: Sebuah Risalah tentang Perjalanan Gastronomi dan Hakikat Identitas - Gerson Ralph Manuel Kho; Zera Edenzwo Subandi; Surianto; Steven Theodore Alexander (Jurnal Spektrum Komunikasi, 2025)
Sudirman Street in Bandung has become a unique phenomenon in the urban landscape of Indonesia. As a popular culinary district, it draws attention due to the presence of non-halal food amidst a predominantly Muslim population. This condition raises questions about how cultural tolerance, religious identity, and economic dynamics interact in public spaces. This study employs the social-identity theory and the concept of a gastronomic city, using direct observation and literature review methods to analyze the cultural negotiation processes that occur. Observation was conducted to understand the social dynamics of the area, while the literature review was used to strengthen the theoretical analysis. The findings reveal that tolerance in this area is pragmatic, managed through space segmentation between halal and non-halal dining areas, as well as social norms emphasizing respect for individual beliefs. Furthermore, this area functions as a representation of a gastronomic city, where cross-cultural experiences are presented through culinary exploration. This study contributes to academic discourse on the formation of tolerance spaces in urban contexts, particularly in areas with cultural and religious pluralism. Thus, Sudirman Street is not merely a culinary hub but also a social negotiation space that reflects the flexibility of identity and urban societal harmony